Surgical Epicondylar Axis of the Knee and Its Relationship to the Axial Tibia Alignment in Knee Osteoarthritis: The Concept of Proximal Twist Tibia - Farinelli, Luca; Baldini, Marco; Faragalli, Andrea; Carle, Flavia; Ulisse, Serena; Gigante, Antonio (The Journal of Knee Surgery, 2021)
The proximal tibia and distal femur are intimately linked with the biomechanics of the knee and they are to be considered in total knee arthroplasty (TKA). The aim of the present study was to evaluate the proximal tibial torsion (PTT) in relation to surgical epicondylar axis (SEA) in a healthy cohort and a pathological cohort affected by knee osteoarthritis (OA). We retrospectively analyzed computed tomography of OA knee of 59 patients before they underwent TKA and nonarthritic knee of 39 patients as control. Posterior condylar angle (PCAn), femoral tibial torsion (SEA-proximal tibial condyle [PTC] and SEA-PTT), PTT (PTC-PTT and posterior condylar axes [PCAx]-PTC), and distance between tibial tuberosity and the trochlear groove (TT-TG) were measured. No differences were found for gender, age, TT-TG, and PCAn angles. Statistically significant differences were found for all the other angles considered. Significant correlation was found between tibial torsion and SEA-PTT angles, between PCAx-PTC and SEA-PTC, between SEA-PTT and SEA-PTC, and between PCAx-PTC and SEA-PTT. All measures, except TT-TG and PCAn angles, showed high validity (area under the curve [AUC] > 75%) in associating with OA, with SEA-PTT displaying the highest validity with an AUC of 94.38%. This is the first study to find significant differences in terms of proximal tibia geometry and anatomy between nonarthritic and OA knees. From our results, we reported that OA group was characterized by a greater internal rotation of tibia with respect to SEAs compared with control group. Since the design of the study cannot evaluate a cause–effect relationship, further studies need to be performed to assess the potential implications of these anatomic differences for knee OA and arthroplasty surgeries.
Keywords: knee arthroplasty; osteoarthritis; tibia alignment; proximal tibial torsion; surgical epicondylar axis